Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja UMKM di Kecamatan Telukjambe Timur - Adawiyah, Dinah Siti Rubai’ah; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a significant role in the Indonesian economy. In 2021, MSMEs contributed 61.07% to the Gross Domestic Product (GDP) and absorbed 97% of the total workforce. This study aims to explore the impact of financial literacy and financial inclusion on the performance of MSMEs in East Telukjambe District. The method used is a quantitative approach using primary data collected through the distribution of questionnaires to 30 MSME actors in East Telukjambe District. Sampling was carried out in a simple random sampling manner. The research data was analyzed using multiple linear regression tests with the help of SPSS software. The results of the study show that financial literacy and financial inclusion have a significant influence on the performance of MSMEs in East Telukjambe District.